Resveratrol isoforms and conjugates: A review from biosynthesis in plants to elimination from the human body - Riccio, Bruno V. F. [UNESP]; Spósito, Larissa [UNESP]; Carvalho, Gabriela C. [UNESP]; Ferrari, Priscileila C.; Chorilli, Marlus [UNESP] (Wiley, 2020)
The natural isomers of resveratrol, cis- and trans-resveratrol, are natural phenolic substances synthetized via the shikimate pathway and found in many sources, including grapes, peanuts, blackberries, pistachios, cacao, cranberries, and jackfruits. They have functional and pharmacological properties such as anticarcinogenic, antidiabetic, anti-inflammatory, and cardioprotective activities. The aim of this article is to review the data published on resveratrol and its isomers, and their biosynthesis in plants, food sources, health and toxic effects, and the excretion of their metabolites. Due to its contribution to the promotion of human health, it is convenient to gather more knowledge about its functional properties, food sources, and the interactions with the human body during the processes of eating, digestion, absorption, biotransformation, and excretion, to combine this information to improve the understanding of these substances.
Keywords: anti-inflammatory activity; anticancer activity; antimicrobial activity; photoreactivity; synthesis